Multiple system morbidities associated with children with snore symptom12. Issue 4 (21st August 2012) - Cai, Xiao‐Hong; Li, Xiu‐Cui; Hu, Qing‐Qing; Yu, Chen‐Yi; Zhou, Yong‐Hai; Su, Miao‐Shang; Zhao, Ya‐Ping; Hu, Yun‐Liang; Wang, Liang‐Xing
Abstract Objective To exam the relationship between snoring and morbidities of multiple systems in children. Study design Children with snoring were enrolled and divided into primary snorer (PS) group and obstructive sleep apnea hypopnea syndrome (OSAHS) group based on polysomnography. The healthy children served as the control group. The growth parameters, maxillofacial malformations, blood chemistry, electrocardiogram, and echocardiogram were recorded and intelligence testing was performed in the enrolled children who were ≥6 years old. Results The weight and height were similar in the control group (n = 60) and the PS group (n = 63), but lower in the OSAHS group (n = 89; P < 0.001). Occurrence of adenoidal face and dental malocclusion in the OSAHS and the PS group was significantly higher than that in the control group (P < 0.001). Compared with the control group, the OSAHS group had a lower serum high‐density lipoprotein cholesterol level, higher low‐density lipoprotein cholesterol level; and a possible higher pulmonary artery pressure based on the echocardiogram (P < 0.001). All the above parameters in the PS group were similar to those in the control group. Full‐scale IQ and performance IQ of the OSAHS group was lower (P < 0.001), attention deficits were significantly higher in the OSAHS group (P < 0.001), but were similar in the PS group when compared to the control group. Conclusions OSAHS in children is associated with delayed growth, maxillofacial malformations, impaired cognitive functions, abnormalities in lipid metabolism, and changes in pulmonary artery pressures. PS children also have higher incidence of maxillofacial malformations but have a normal growth and normal cognitive functions. Pediatr Pulmonol. 2013; 48:381–389. © 2012 Wiley Periodicals, Inc.